2006
DOI: 10.1111/j.1525-1438.2006.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body positron emission tomography and tumor marker CA125 for detection of recurrence in epithelial ovarian cancer

Abstract: We evaluated the clinical role of the combination of positron emission tomography (PET) with F-18 fluorodeoxyglucose (FDG) and tumor marker CA125, in the detection of recurrence after initial therapy for epithelial ovarian cancer. The indication is the cases that cannot be confirmed the recurrence by conventional imaging modalities. Ninety patients underwent PET and computed tomography, including the measurement of specific tumor markers. FDG-PET confirmed recurrence in 46 patients (51%), and the recurrent sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The rates of NPV, specificity, PPV, and sensitivity of planned versus actual treatment reported in this study (83.3, 55.6, 76.9 and 93.0%, respectively) showed a good efficacy of this procedure in planning surgical treatment in advanced recurrent ovarian cases. The false-negative rate (7.1%) observed in this study compares well to data reported in the literature [22, 23, 26] and can be explained with the miliary tumor diffusion on the peritoneal surface and the small amount of ascites in our series. However, the existence of false-negative (n = 3) and false-positive cases (n = 13) with respect to the possibility of optimal cytoreduction should be considered.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The rates of NPV, specificity, PPV, and sensitivity of planned versus actual treatment reported in this study (83.3, 55.6, 76.9 and 93.0%, respectively) showed a good efficacy of this procedure in planning surgical treatment in advanced recurrent ovarian cases. The false-negative rate (7.1%) observed in this study compares well to data reported in the literature [22, 23, 26] and can be explained with the miliary tumor diffusion on the peritoneal surface and the small amount of ascites in our series. However, the existence of false-negative (n = 3) and false-positive cases (n = 13) with respect to the possibility of optimal cytoreduction should be considered.…”
Section: Discussionsupporting
confidence: 78%
“…In the last years, FDG-PET/CT has been utilized to identify clinically occult recurrent ovarian cancer, inorder to improvethe earlier detection of relapse and consequently increase the possibility of secondary cytoreduction [17,18,19,20,21,22,23,24,25,26]. The accuracy rate has ranged from 70 to 95%, and it is limited by the inability to detect small volume (≤7 mm) disease and the misinterpretation of normal physiological abdominal activity [17, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT sensitivity is reported to be especially low for detection of peritoneal carcinosis and lymphatic metastases which is not so for FDG PET. In this regard, in a series by Murakami et al including 90 patients, FDG PET had a sensitivity for the detection of intraperitoneal and retroperitoneal metas-tases of ovarian cancer of 93.9 and 92.9 %, respectively [42]. Furthermore, FDG PET imaging was able to detect metastases in normal-sized lymph nodes.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…This is useful in cases where conventional imaging fails to detect recurrent disease [27]. FDG-PET may be more useful in detecting recurrence in the setting of negative conventional imaging studies and an increasing CA-125 [28]. In patients with an asymptomatic increase of CA-125, PET has a sensitivity of 87.5%.…”
Section: Ovarian Cancermentioning
confidence: 99%